The Effect of Health Education Using Booklet Media on Knowledge of Emergency Handling Among Students - Agus Riyanto; Johanes Sapri; Eko Risdianto; Yuliza Andriyani Siregar (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
First aid in emergency situations can occur in the surrounding environment, requiring serious and proper handling to prevent more fatal risks if the handling is not according to procedures. Health education and promotion can use various media, and one such medium is a booklet. The model in this study is quantitative research. The research design uses an experimental method. The sample was purposively selected, consisting of 64 students. Data were analyzed using SPSS. The results showed that in the control group, there were 0% in the very low category, 12.5% in the low category, 56.25% in the moderate category, 25% in the high category, and 6.25% in the very high category. In the treatment group, 0% were in the very low category, 12.5% in the low category, 18.75% in the moderate category, 37.5% in the high category, and 31.25% in the very high category. Thus, it can be stated that the emergency handling knowledge of students in the treatment group using the booklet showed high and very high average scores. The analysis test showed a significance value of 0.014 (p<0.05), indicating that there is an effect of health education using booklet media on first aid knowledge. For educational institutions, it is recommended to incorporate supporting media such as booklets tailored to the needs and objectives of health education.